THE USE OF SOCIAL MEDIA AS A ONLINE MEDIUM OF DEAF CHILDREN (STUDY OF FACEBOOK) - Sinta Swastikawara (Jurnal Nomosleca, 2018)
AbstractThe use of Facebook for deaf children has become a breakthrough in the existence of "normal" group dominance over access to online media. Deaf children are no longer confined to their offline environment which tends to be restricted. But on the other hand, the use of social media also affects the exploitation of their identity online. Based on this, this study aims to explore the use of social media as an online intermediary for deaf children. Researchers use case study methods and also the concept of self disclosure and computer mediated communication to analyze. The results of this study indicate that the form of Facebook accounts is a form of self-disclosure of deaf children in conveying their data information online to friends online. Likewise with their interaction on Facebook which is also a form of their openness in making friends online on Facebook. Furthermore, media literacy knowledge owned by deaf children makes them more protective of the disclosure of their personal data information on Facebook. Self-disclosure in the delivery of personal data information and in establishing relationships in the online world for deaf children carried out with control creates selectivity in self-disclosure in Facebook.Keywords : used of media, social media, childrenDOI : https://doi.org/10.26905/nomosleca.v4i2.2370